Prognostic impact of ß-blocker use in patients with stable coronary artery disease. Issue 22 (19th June 2014) - Bauters, Christophe; Lemesle, Gilles; Meurice, Thibaud; Tricot, Olivier; de Groote, Pascal; Lamblin, Nicolas
Abstract : Objective: To assess the association of ß-blocker use with cardiovascular mortality in patients with stable coronary artery disease (CAD). Methods: We analysed the data of 4184 outpatients included in a prospective cohort study on stable CAD. Two groups were formed based on ß-blocker use at enrolment. Two propensity score analyses were performed to control for differences in covariates: one with adjustment among the entire cohort, and the other with propensity score matching. The outcome variable was cardiovascular mortality after a 2-year follow-up. Results: There were 3320 patients with ß-blocker use. Younger age, hypertension, diabetes, prior myocardial infarction, multivessel CAD, prior coronary revascularisation, prior stroke, prior hospitalisation for heart failure and a low LVEF were associated with ß-blocker use. Clinical follow-up data were obtained for 4149 patients (99.2%). When adjusted on propensity score, ß-blocker use was associated with a HR for cardiovascular mortality of 0.64 (0.42–0.98) in the whole cohort (p=0.04). After one-to-one propensity score matching, both groups (n=839 in each group) were well matched on covariates. The cardiovascular mortality rate in the propensity-matched cohort was significantly lower in patients with ß-blocker use with a HR of 0.43 (0.22–0.82) (p=0.011). Non-cardiovascular mortality was similar in both groups. These results were consistent across different subgroups. Conclusions: In this observational study of patients with stable CAD, the use of ß-blockers was associated with a lower risk of cardiovascular mortality.